Critical issues affecting the service quality in water-based tour operator : a case study of marine leisure tourist guide in Andaman Cluster, Thailand - Phimnada Fowler (Prince of Songkla University, 2015)
Thesis (M.B.A., (Hospitality and Tourism Management (International Program)))--Prince of Songkla University, 2012